Recovering multiscale buried anomalies in a two-layered medium. (15th September 2015) - Li, Jingzhi; Li, Peijun; Liu, Hongyu; Liu, Xiaodong
Abstract: We develop an inverse scattering scheme of recovering impenetrable anomalies buried in a two-layered medium. The recovery scheme works in a rather general setting and possesses several salient features. It makes use of a single far-field measurement in the half-space above the anomalies, and works independently of the physical properties of the anomalies. There might be anomalous components of multiscale sizes presented simultaneously. Moreover, the proposed scheme is of a totally direct nature without any inversion involved, and hence it is very fast and robust against measurement noise. Both theoretical foundation and numerical experiments are presented. This extends related results in the literature on recovering multiscale scatterers located in a homogeneous space.